Research ethics for scientists : a companion for students - Stewart, C. Neal, Jr (John Wiley & Sons, 2011)
Research Ethics for Scientists is about best practices in all the major areas of research management and practice that are common to scientific researchers, especially those in academia. Aimed towards the younger scientist, the book critically examines the key areas that continue to plague even experienced and well-meaning science professionals. For ease of use, the book is arranged in functional themes and units that every scientist recognizes as crucial for sustained success in science; ideas, people, data, publications and funding. These key themes will help to highlight the elemen.